Exploring the Success of Implementing Project-Based Learning Model in Accounting Learning Material - Andalusia, Balqis; Suranto, Suranto; Haque, Farhat (Universitas Pendidikan Mandalika, 2024)
This study aims to explore the success of implementing the Project Based Learning (PjBL) model in the elements of Service, Trade, and Manufacturing Company Accounting. The approach used in this research was qualitative with a case study method. This research selected one vocational school with high integrity, namely SMKN 1 Banyudono, with several informants consisting of students in Financial and Institutional Accounting classes, Accounting Teachers, and the School Principal. Data collection methods included interviews, observations, and documentation studies, with data validity tested through technique triangulation and source triangulation. The collected data was analyzed through three activities: data reduction, data presentation, and drawing conclusions or verification. The results showed that PjBL had a positive impact on students' learning outcomes, the quality of learning, and learning motivation. However, its weakness laid in requiring longer project implementation time and preparation. Nevertheless, PjBL can create an innovative learning environment, make graduates more prepared for the industrial world, and have a positive impact on students' learning outcomes and the quality of learning.